Stability of Maleimide-PEG and Mono-Sulfone-PEG Conjugation to a Novel Engineered Cysteine in the Human Hemoglobin Alpha Subunit - Cooper, Chris E.; Bird, Matthew; Sheng, XiaoBo; Choi, Ji-Won; Silkstone, Gary G.A.; Simons, Michelle; Syrett, Natalie; Piano, Riccardo; Ronda, Luca; Bettati, Stefano; Paredi, Gianluca; Mozzarelli, Andrea; et al. (Frontiers in Chemistry, 2021)
In order to use a Hemoglobin Based Oxygen Carrier as an oxygen therapeutic or blood substitute, it is necessary to increase the size of the hemoglobin molecule to prevent rapid renal clearance. A common method uses maleimide PEGylation of sulfhydryls created by the reaction of 2-iminothiolane at surface lysines. However, this creates highly heterogenous mixtures of molecules. We recently engineered a hemoglobin with a single novel, reactive cysteine residue on the surface of the alpha subunit creating a single PEGylation site (betaCys93Ala / alphaAla19Cys). This enabled homogenous PEGylation by maleimide-PEG with > 80% efficiency and no discernible effect on protein function. However, maleimide-PEG adducts are subject to deconjugation via retro-Michael reactions and cross-conjugation to endogenous thiol species in vivo. We therefore compared our maleimide-PEG adduct with one created using a mono-sulfone-PEG less susceptible to deconjugation. Mono-sulfone-PEG underwent reaction at alphaAla19Cys hemoglobin with > 80% efficiency, although some side reactions were observed at higher PEG:hemoglobin ratios; the adduct bound oxygen with similar affinity and cooperativity as wild type hemoglobin. When directly compared to maleimide-PEG, the mono-sulfone-PEG adduct was significantly more stable when incubated at 37°C for seven days in the presence of 1 mM reduced glutathione. Hemoglobin treated with mono-sulfone-PEG retained >90% of its conjugation, whereas for maleimide-PEG < 70% of the maleimide-PEG conjugate remained intact. Although maleimide-PEGylation is certainly stable enough for acute therapeutic use as an oxygen therapeutic, for pharmaceuticals intended for longer vascular retention (weeks-months), reagents such as mono-sulfone-PEG may be more appropriate.